Development of Automated Egg Incubator With Backup Power Supply - Maroma, Allen N.; Maroma, Dolly P.; Pangilinan, Bernardo A. (UI Scholars Hub, 2023)
This study addresses the development of an automated egg incubator with backup power supply that could benefit farmer communities through the developmental research approach. A prototype is developed to respond to the needs for uninterrupted incubation which is affected by the frequent power outages that reduce its efficiency in egg handling. In this project, the automated egg incubator with a backup power supply is designed to hatch a capacity of 150 eggs (75 setters and 75 hatchers) every 21 days, ensuring continuous operation even in the absence of a consistent power supply. An inverter, connected to a battery, ensures a 12 hr uninterrupted power supply, maintaining a warm internal environment. The thermostat-controlled heater regulates the incubator’s temperature within the range of 36 °C–38 °C. In case of a power outage, the incubator can seamlessly switch to grid power during brownouts, maintenance, or the rainy season. Based on rigorous testing, the incubation period is confirmed at 21 days, with an initial hatch rate of 70%, increasing to 80% in subsequent tests. The average chick weight, measured a few hours after hatching, stands at 40.8 g. To assess its practical impact, the researchers extended the device to a local game-fowl farmer, resulting in substantial income generation and improved breeding efficiency. Beyond direct economic benefits, the automated egg incubator represents a novel technological achievement, showcasing how science and technology can empower communities, foster economic growth, and contribute to the greater good within a practical context.